The governance of schools for internally displaced learners in Puntland, Somalia: a top-down or bottom-up approach to education peacebuilding? - Ramaite, Adivhaho Florence (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
This study examines educational governance in schools for internally displaced learners in Puntland, Somalia. Many Somalis have been internally displaced from the south and central of Somalia and neighbouring regions because of armed insurgence, as well as climate and ecological disasters. Communities of internally displaced Somalis who have settled in the north-eastern region of Somalia, together with the Ministry of Education and nongovernmental organisations such as Relief International, have established schools for internally displaced learners. The study uses interviews with teachers, school principals and school committee members to examine their experiences of how schools are governed, specifically in terms of the bottom-up and top-down approaches to peacebuilding education. This research study is the first of its kind to examine the experiences of education actors in internally displaced person schools in Somalia. It provides crucial, new information on northern NGOs and how they shape the governance of knowledge and resources in Somali schools and how Somali education actors interpret and respond to these interventions. Drawing on education studies and international relations, it develops a transdisciplinary framing of peacebuilding education and specifically focuses on the top-down and bottom-up approaches to peacebuilding education provision. It weaves these two disciplinary perspectives together to help establish the implications of the security sector in education and broadly post-conflict reconstruction. The study finds that donors, international NGOs and government actors use a top-down approach to education, which may sit at odds with local needs and priorities. It finds that Somali knowledge and values are marginalised in the curriculum and teachers' professional development and that the distribution of resources such as teacher salaries and school feeding programmes is fragmented, opaque and lacking in accountability. The study emphasises that the exclusion of local voices may further contribute to the causes underlying conflict.
Keywords: Peace-building -- Somalia -- Puntland; Internally displaced persons -- Education -- Somalia -- Puntland; School management and organization -- Somalia -- Puntland; Educational governance; Top-down and bottom-up design